The built heritage sector in Portugal: Education in conservation and professionalization - Genin, S. M.; Brum, P. (Professionalism in the built heritage sector, 2019)
In the built heritage sector in Portugal, regarding professional training for contractors and craftsmen there is no specific preparation on Conservation as it focuses exclusively on new construction. As far as academic education is concerned, Master’s degree courses offer some subjects, but generally optional. Recently, there has been an increase in multidisciplinary advanced training, as recommended in the Principles for Capacity Building through Education and Training in Safeguarding and Integrated Conservation of Cultural Heritage, draft by CIF-ICOMOS. However, neither the professional associations nor the existing legislation require these skills before professional practice. This article analyses and discusses professional training and academic education in the built heritage sector in Portugal, as well as the legislation governing the professional practice.